SLR on Geopolitical Risk, Commodities, Crypto, and Stocks - Iman Lubis; Hamidah Hamidah; I Gusti Ketut Agung Ulupui Ulupui (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study conducts a Systematic Literature Review (SLR) to explore the impact of Geopolitical Risk (GPR) on financial markets, focusing on stock returns, gold, oil, and cryptocurrencies. Motivated by increasing global tensions and the complexity of cross-asset dynamics, the study aims to synthesize empirical evidence from 64 peer-reviewed journals published between 2020 and 2025. Using PRISMA guidelines, the review identifies five dominant themes: the role of gold and crypto as safe havens, sectoral and regional asymmetries in GPR spillovers, and the moderating role of ESG in crisis periods. Findings show that GPR intensifies volatility and spillover effects, especially during systemic crises, with different asset reactions under geopolitical versus economic shocks. Gold remains a relatively reliable hedge, while crypto offers short-term diversification with high uncertainty. Methodological gaps, such as the underuse of non-linear models and lack of studies in emerging markets, are also highlighted. The study contributes to global finance literature by mapping asset behavior under geopolitical stress and suggesting future research directions using advanced modeling in underexplored regions. Keywords: Geopolitical Risk; Gold; Oil; Cryptocurrency; Financial Volatility